2020
DOI: 10.1007/s00134-020-06226-9
|View full text |Cite
|
Sign up to set email alerts
|

Positive end-expiratory pressure-induced recruited lung volume measured by volume-pressure curves in acute respiratory distress syndrome: a physiologic systematic review and meta-analysis

Abstract: Purpose: Recruitment of lung volume is often cited as the reason for using positive end-expiratory pressure (PEEP) in acute respiratory distress syndrome (ARDS) patients. We performed a systematic review on PEEP-induced recruited lung volume measured from inspiratory volume-pressure (VP) curves in ARDS patients to assess the prevalence of patients with PEEP-induced recruited lung volume and the mortality in recruiters and non-recruiters. Methods: We conducted a systematic search of PubMed to identify studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In this way, early alveolar closure can be avoided, and some alveoli that lose ventilation function due to exudation, atelectasis, and other reasons will expand so that the reduced functional residual volume will increase, and the purpose of improving blood oxygen can be achieved [ 10 ]. PEEP is similar to intermittent positive pressure respiration, but because of its longer duration of action, it has a wider range of effects on the respiratory and circulatory systems [ 11 ]. PEEP is the external pressure applied to the airway by the ventilator at the end of the patient's expiratory breath during mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, early alveolar closure can be avoided, and some alveoli that lose ventilation function due to exudation, atelectasis, and other reasons will expand so that the reduced functional residual volume will increase, and the purpose of improving blood oxygen can be achieved [ 10 ]. PEEP is similar to intermittent positive pressure respiration, but because of its longer duration of action, it has a wider range of effects on the respiratory and circulatory systems [ 11 ]. PEEP is the external pressure applied to the airway by the ventilator at the end of the patient's expiratory breath during mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial proportion of patients with coronavirus disease (COVID-19) admitted to the ICU require invasive mechanical ventilation for acute respiratory distress syndrome (ARDS), which is still associated with a high mortality rate ( 1 ). Applying the optimal positive end-expiratory pressure (PEEP) to ensure lung recruitment while limiting lung hyperinflation remains challenging in ARDS ( 2 , 3 ). Yet, there are a few simple tools that might help personalize the level of PEEP in those patients at the bedside.…”
mentioning
confidence: 99%
“…Yet, there are a few simple tools that might help personalize the level of PEEP in those patients at the bedside. Among them, the lung ultrasound (LUS) aeration score and the recruitment-to-inflation (R/I) ratio have the potential to identify patients who are more likely to benefit from PEEP ( 2 ). Previous studies indeed suggested that LUS could assess spatial distribution of PEEP-induced lung recruitment but does not reliably detect hyperinflation ( 4 , 5 ).…”
mentioning
confidence: 99%
“…It is widely appreciated that ARDS is a heterogeneous disorder and that many patients with ARDS may have little or no potential for lung recruitment [16][17][18]. Higher PEEP may well be harmful in such patients whether or not they have COVID-19 [19].…”
mentioning
confidence: 99%